Facing the Dictators: Anthony Eden, the Foreign Office and British Intelligence, 1935–1945. Issue 4 (3rd July 2020) - Lomas, Daniel W. B.
Abstract: This article uses the inter-war and wartime career of Anthony Eden, as a vehicle to understand the little understood relationship between secret intelligence, British Foreign Secretaries and the Foreign Office. While secret intelligence is no longer the 'missing dimension', it once was in studies of diplomatic and political history, its use by British Foreign Secretaries remains a neglected subject. The article also sheds important new light on the Foreign Office's wartime use of intelligence, especially diplomatic signals intelligence (SIGINT), a subject often overshadowed by the use of military SIGINT from Bletchley Park, showing the close relationship between intelligence officials and British diplomats in guiding British foreign policy. As Foreign Secretary in the 1930s and 1940s, Eden showed himself to be a skilful reader of intelligence reports, using this information as he went about crafting Britain's policy towards the increasingly bellicose powers of Nazi Germany, Fascist Italy and Imperial Japan.